Contemporary issues on marriages: an analysis - Mahmud , Mek Wok (IIUM Press, 2011)
Marriage in Islam is a contract of duties and responsibilities between two partners who have given their full and free consent to marry each other. Marriage is regarded as the norm for all, a safeguard on chastity and essential to the growth and stability of the family. The objective of this study is to analyze the contemporary issues pertaining to marriage and its underlying effects in Muslim societies. Issues such as financial disability, different understanding of parenting and Islam, stress, domestic violence, sexual dysfunction, intercultural marriage and so forth are discussed as well the possible solutions. Understanding of those issues will bring peace and tranquility to the life of Muslim couples.